Food in the social order : studies of food and festivities in three American communities - Douglas, Mary, 1921-2007 (Douglas, Mary, 1921-2007. Works. 2003, 2003)
First published in 1984, This work is a cross-cultural study of the moral and social meaning of food. It is a collection of articles by Douglas and her colleagues covering the food system of the Oglala Sioux, the food habits of families in rural North Carolina, meal formats in an Italian-American community near Philadelphia. It also includes a grid/group analysis of food consumption.